Pengaruh Budaya Organisasi dan Komunikasi Kerja Terhadap Kinerja Pegawai Dinas Perhubungan - Vera Anitra; Liliq Lestary; Rinda Sandayani Karhab (Forum Kerjasama Pendidikan Tinggi (FKPT), 2024)
Human resources in an institution are included in the determining aspects in the dynamic development process. A greater contribution is needed, especially in the implementation of government by improving employee performance. Organizational culture and work communication are included in the aspects that influence employee performance. This study aims to measure the influence of Organizational Culture and Work Communication on Employee Performance at the East Kalimantan Provincial Transportation Agency. This type of research uses quantitative research methods. The data collection technique in this study is by using a questionnaire distributed to all employees with Honor status, with a population of 58 employees. The analysis technique used in this study is the non-probability sampling technique, namely by using the saturated sampling method. The sampling technique is carried out using saturated sampling by taking the entire population of 58 employees. The data were analyzed using multiple linear regression analysis methods, the data processing of this study used the SPSS (Statistical Product and Service Solutions) version 29 program. The results show that the influence of organizational culture on performance obtained a T-statistic value of 2.927 and a p-value of 0.005 where the value so that H1 is accepted. The Influence of Communication on Employee Performance obtained a T-statistic value of 2.147 and a p-value of 0.036 where the value so that H2 is accepted. The Influence of Organizational Culture and Work Communication on Employee Performance obtained a T-statistic value of 31.873 and a p-value of 0.001 where the value so that H3 is accepted.